2014
DOI: 10.1094/php-br-13-0129
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Resistance to Powdery Mildew in the Hop Cultivars Newport and Comet

Abstract: Hop powdery mildew, caused by Podosphaera macularis, is an important disease in the Pacific Northwest. Resistant cultivars of hop have been developed and have provided field immunity to the disease until virulent strains of P. macularis emerged. Due to the increase of powdery mildew on formerly resistant cultivars, studies were conducted to characterize potential sources of host resistance. Accepted for publication 5 February 2014. Published 27 March 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…R6-virulent isolates of the fungus are now broadly established in the U.S. Pacific Northwest but were not confirmed in isolates derived from the Upper Midwest or eastern United States. Although diseased leaves of cultivars identified as Newport and Nugget were received from outside of the Pacific Northwest, both of which are reported to possess R6 (Wolfenbarger et al 2014a), R6 virulence was unable to be confirmed in this work. The lack of R6 virulence in these isolates may reflect the presence of susceptible, off-type cultivars (i.e., cultivars other than Nugget or Newport) in the yards where the samples were collected because it is common for contamination of rootstock to occur in hop yards due to the crop being vegetatively propagated.…”
Section: Discussionmentioning
confidence: 61%
“…R6-virulent isolates of the fungus are now broadly established in the U.S. Pacific Northwest but were not confirmed in isolates derived from the Upper Midwest or eastern United States. Although diseased leaves of cultivars identified as Newport and Nugget were received from outside of the Pacific Northwest, both of which are reported to possess R6 (Wolfenbarger et al 2014a), R6 virulence was unable to be confirmed in this work. The lack of R6 virulence in these isolates may reflect the presence of susceptible, off-type cultivars (i.e., cultivars other than Nugget or Newport) in the yards where the samples were collected because it is common for contamination of rootstock to occur in hop yards due to the crop being vegetatively propagated.…”
Section: Discussionmentioning
confidence: 61%
“…Before 2012, PM races present in the US Pacific Northwest possessed non‐v4/v6 virulence genes, and USDA 21087M was resistant to PM (Wolfenbarger et al, 2014). Since 2012, v4/v6 PM races have prevailed, thus ensuring susceptibility of 21087M.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the question concerning whether or not two R-genes are working in conjunction for resistance to PM is confounded by the presence of two potential R-genes (R4 and R6) loci in the same resistant parent genotype. The female parent of this cross, USDA Newport, appears to possess both R4 and R6 genes (Wolfenbarger et al 2014) for resistance to PM. Later work by Wolfenbarger et al (2016) suggests that R4 and R6 may be misclassified, the same gene, or so tightly linked that they segregate as a single group.…”
Section: Gene Identificationmentioning
confidence: 99%